2012
DOI: 10.1016/s1413-8670(12)70299-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for cervical intraepithelial neoplasia among HIV-infected women

Abstract: Severity of immunosuppression, presence of HPV infection and younger age are strong predictors of CIN among HIV-infected women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…HPV-35 was the most prevalent in seropositive women with a frequency of 49.4%. Our results are in agreement with previous studies which reported that the prevalence of HPV infection is higher among HIV-seropositive women 1522. In Tanzania and South Africa Dols et al23 reported that the most frequent HPV-HR in HIV positive women were HPV-52 (30%) and HPV-16 (26%), there was no regional difference in the prevalence of HPV-18 and HPV-35.…”
Section: Discussionsupporting
confidence: 93%
“…HPV-35 was the most prevalent in seropositive women with a frequency of 49.4%. Our results are in agreement with previous studies which reported that the prevalence of HPV infection is higher among HIV-seropositive women 1522. In Tanzania and South Africa Dols et al23 reported that the most frequent HPV-HR in HIV positive women were HPV-52 (30%) and HPV-16 (26%), there was no regional difference in the prevalence of HPV-18 and HPV-35.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our study findings are in accordance with a very recent study in which the investigators observed similar rates of HPV infection and cervical pathology 10. Moreover, in studies among HIV-infected women in Sao Paolo, Rio De Janeiro, and Belo Horizonte, Brazil, 13%, 24%, and 24% had a diagnosis of squamous intraepithelial lesions, respectively 1113. In studies in Cambodia, Thailand, and People’s Republic of China, the prevalence of HSIL/LSIL among women attending HIV clinics was 17%, 16%, and 8%, respectively 8,14,15.…”
Section: Discussionsupporting
confidence: 92%
“…The absence of significant associations could be explained by the lack of power to detect these associations. Nevertheless, the degree of immunosuppression is expected to have an effect on the incidence and progression of squamous intraepithelial lesions among HIV-infected women as it has been shown in several observational studies 1317. To date, evidence on an independent association between ART and the natural history of HPV infection or the risk of squamous intraepithelial lesions and cervical cancer is contradictory and inconclusive 1821.…”
Section: Discussionmentioning
confidence: 99%
“…Increased metaplastic activity in the cervix during adolescence and its decline after menopause implica earlier age at sexual debut as a risk factor for HPV infection. Other factors related to HPV infection or persistence include young age, the socioeconomic status, multiparity, male circumcision, condom use, oral contraceptive use, smoking, immune suppression, viral load, and certain genetic polymorphisms 26, 91, 73, 89, 34, 32, 71, 83, 86, 30 40, 62, 82, 69, 68, 11, 67, 35, 61 90, 72, 66, 54, 6, 84, 59, 43 44, 31, 42, 45, 74, 33, 81, 70 51, 58, 53, 56 52 18 16 in the human leukocyte antigen system (Moscicki et al, 2001;Palefsky et al, 2001;Maciag et al, 2002;Schlecht et al, 2002;Richardson et al, 2003;Winer et al, 2003;Baldwin et al, 2004;Baseman and Koutsky, 2005;Cotton et al, 2007;Goodman et al, 2008;Tobian et al, 2009;Tobian et al, 2010;Marks et al, 2011;Bahmanyar et al, 2012;Emeka et al, 2012;Liao et al, 2012;Repp et al, 2012;Schabath et al, 2012;Teixeira et al, 2012;Zhang et al, 2012).…”
Section: Epidemiology Of Human Papillomavirus Infectionsmentioning
confidence: 99%